Cardiac tamponade - distinguishing traumatic and non-traumatic causes - the role of forensic pathology - Hasim, Husna Syaza; Mohd Mussadik, Umul Khairil Fatimah; Zaki, Hafizatul Solehah; Chng, Kay Ly (Malaysian Society of Pathologists, 2025)
Introduction: Cardiac tamponade is a critical medical condition caused by the accumulation of fluid in the pericardial sac, which leads to increased intrapericardial pressure. This pressure impairs cardiac contractility and reduces cardiac output, making timely diagnosis and rapid intervention crucial for survival. Without prompt treatment, cardiac tamponade often results in sudden death. Cardiac tamponade can arise from either traumatic or non-traumatic causes. Traumatic sources include blunt trauma to the chest, complications from cardiac procedures, and even cardiopulmonary resuscitation. Non-traumatic causes often involve conditions such as post-myocardial infarction, thoracic aortic dissection, and pericarditis. A thorough post-mortem examination is crucial in coming into a precise conclusion, distinguishing between a traumatic and a non-traumatic cause.